The Use of Videocast in Improving the Speaking Ability Integrated in a Drama Class - Pradana, Satria Adi (Universitas Islam Negeri Raden Intan Lampung, 2016)
The advancement of technology and information in this age has made a greater influence for English teachers and students in improving their capabilities in utilizing the technology in the teaching and learning process. Because the use of technology has an important role as teaching and learning aid, Videocast is proposed to solve some problems encountered in the teaching of speaking skill. The findings were classified into: students’ scores improvement and the steps of teaching speaking using Videocast in improving the students’ attitude. The improvement of the students’ score can be seen in the increased score of the students’ speaking from the preliminary study and the score after the implementation of the teaching of speaking using Videocast in the first Cycle. The students’ average score in the preliminary study was 60.03, while the average score in the end of implementation of this study was 72. More specifically, 20 students out of 20 (100%) got higher than or equal to 60 in the end of the study while in preliminary study 11 students out of 20 (55%) got the score higher or equal to 60. After the implementation of Videocast in the class, it is expected that all of the students reached the score at least 60 equal or above (C+). Considering the fact that the class is heterogenic means that there is students’ classification based on their level of knowledge and skill, the criteria of achieving the success is rendered exactly 100%. It is determined that for Drama subject in IAIN Raden Intan Lampung, the range of score for 55-59 is (C) followed by 60-64 (C+). The result shows that 100% of the students had achieved the equal or higher than 60 in the first Cycle.